2015
DOI: 10.1111/lam.12407
|View full text |Cite
|
Sign up to set email alerts
|

Identification of estrone-degrading Betaproteobacteria in activated sludge by microautoradiography fluorescent in situ hybridization

Abstract: Estrone (E1) is one of the natural estrogens, which can be degraded but is not always completely removed in wastewater treatment plants. E1 is suspected of causing the endocrine disruption of aquatic organisms in the receiving water body. We identified dominant E1-incorporating bacteria, which should include E1-degrading bacteria, in activated sludge treating domestic wastewater. Sphaerotilus-Leptothrix-related bacteria, which had never been reported in the previous attempts based on culture-dependent approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…frequently employed for in situ identification of microorganisms with specific substrate uptakes (Okabe et al, 2004;Hagman et al, 2008;McIlroy et al, 2010). Despite this, MAR-FISH has only been used as a microbial identification technique for a few micropollutants such as gemfibrozil (Lolas et al, 2012) and estrone (Kurisu et al, 2015;Zang et al, 2008).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…frequently employed for in situ identification of microorganisms with specific substrate uptakes (Okabe et al, 2004;Hagman et al, 2008;McIlroy et al, 2010). Despite this, MAR-FISH has only been used as a microbial identification technique for a few micropollutants such as gemfibrozil (Lolas et al, 2012) and estrone (Kurisu et al, 2015;Zang et al, 2008).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…The microautoradiography-fluorescence in situ hybridization (MAR-FISH) technique was applied to identify active oestrone-assimilating bacteria in activated sludge using [2,4,6,7-3 H(N)]oestrone as a tracer. Some studies have revealed that several active proteobacterial taxa incorporated trace oestrone (submicrogram per litter concentrations) in activated sludges, indicating that the main degraders of oestrogen in wastewater treatment plants are different from those reported in culture-dependent studies (Zang et al, 2008;Thayanukul et al, 2010;Kurisu et al, 2015). However, this technique has several disadvantages.…”
Section: Anaerobic Degradation Of Steroids Through the 23-seco Pathwaymentioning
confidence: 99%
“…FISH is a powerful tool in microbiology. For example, it has been used in the detection of community structures in biofilms (Almeida et al, 2011;Aoi, 2002), aquatic microbiome sampling (Dawson et al, 2012;Kurisu et al, 2015;Medlin and Orozco, 2017), cultural heritage conservation (La Cono and Urzi, 2003;Urzi and De Leo, 2001), in clinical samples of blood sera (Da Silva et al, 2015) and many other uses. FISH has been used for the localisation of bacteria, fungi and viruses within respective hosts (reviewed in (Kliot and Ghanim, 2016)).…”
Section: Introductionmentioning
confidence: 99%